Seksologi Hindu Dalam Lontar Rukmini Tattwa - I Gede Surya Marta Dinata; Ni Komang Sutriyanti; Gek Diah Desi Sentana (Jayapangus Press, 2019)
Health of human reproduction is one of the important things that must be considered as a repair tool for women, the development of the age is increasing, the development of reproductive health disease is very worrying as much we hear now. Health tools must be considered by caring for medical devices themselves. There are many kinds of treatments offered for modern health care. In the religion of sexuality there is a lot of it in the ancient manuscripts which know less, one of them is Lontar Rukmini TattwaThe results of the study: (1) Sexology in Lontar Rukmini Tattwa contains various kinds of health ingredients for self-care and also intimate organs in both men and women. Judging from the contents of the palm leaf, the sexology in Lontar Rukmini Tattwa is a sexology about the health of intimate organs and treatments for the health and beauty of the body. In Lontar Rukmini Tattwa there are approximately 157 types of herbs used to treat self and intimate organs. From approximately 157 types of herbs, the authors group them into 6 types of potions related to their activities, including (1) male and female, 2 ) Potions for beauty care, (3) Potions for bodily ailments, (4) Potions during intercourse, (5) Passion concoctions, (6) Potions to get help. The ingredients in Lontar Rukmini Tattwa use most of the medicinal plants, among others, laos, pepper, manjakane, turmeric, ginger, meeting comedy, temu ireng, sugar cane, grass puzzles, agave, lotus plants, lace. The values ​​contained in Lontar Rukmini Tattwa are Theological Values, Ethical Values, and Social Values.